FAKTOR-FAKTOR YANG MEMPENGARUHI TERLAMBATNYA PENYELESAIAN STUDI PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Nor Amira; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this research was because of so many students of university that overdue in study accomplishment, that means more that eight semesters (five years). The formulation of this research was the factors that effected the overdue in study accomplishment to students and how much the percentage of the factors effects of overdue in study accomplishment to students of social science and politics faculty. While, the purpose of the research was wanted to know the factors that effected the overdue in study accomplishment to students and to know how much the percentage of factors effects to students of social science and politics faculty. This research have been done in social science and politics faculty, university of riau, Pekanbaru. The population in this research was all of students who the time of study more than eight semesters (five years), lecturer, student’s parent and society personage. While, the technique in taking sample the writer used proportional random sampling technique. The technique in collecting data, the writer used questionaire, interviewe and documentation. In analysing the data, the writer used descriptive quantitative method.Based on the result of this research, the writer can concluded that to know what are the factors that effected and how much the percentage of factors effects to students in study accomplishment, the writer analyze the data with formula: . So, we can concluded that the factors that effected the overdue in study accomplishment to students was: 1. Internal factors (physic, psychology, and tiring). 2. External factors (family, university and society). The factors percentage were: internal factors was 73,55% and external factors was 67,27% the category was enough.Key words: factor, effect, the time of study.